Impact of prolonged hotel closures during the COVID-19 pandemic on Legionella infection risks - Molina, Jhon J.; Bennassar, Magdalena; Palacio, Edwin; Crespi, Sebastian (Frontiers in Microbiology, 2023)
In general, it is accepted that water stagnation and lack or poor maintenance in buildings are risk factors for Legionella growth. Then, in theory, the prolonged hotel closures due to the COVID-19 pandemic may have increased the risk of Legionella infections. However, there are very few field studies comparing the level of Legionella colonization in buildings before the pandemic and the new situation created after the lockdown. The objective of this study was to analyze these differences in a group of hotels that experienced prolonged closures in 2020 due to the COVID-19 pandemic. We have studied the Legionella spp. results, analyzed by standard culture, from the domestic water distribution systems of 73 hotels that experienced closures (from 1 to > 4 months) during 2020, immediately after the reopening. The results were compared with those obtained in similar samplings of 2019. For the comparative analysis, we divided the hotels in two groups: Group A that have suffered closures for ≤3 months and Group B that remained closed for more than 3 months, both in relation to the opening period of 2019. In the Group B (36 sites), the frequency of positive samples in the hot water system increased from 6.7% in 2019 to 14.0% in 2020 (p < 0.05). In the Group A (37 sites), no significant differences were observed. No statistically significant differences were observed in terms of positive sites (defined as hotels with at least 1 positive sample), Legionella spp. concentrations and prevalence of Legionella pneumophila sg1 between the samplings of the two periods studied. The results suggest that hotels that suffered the longest prolonged closures (> 3 months) could have carried a higher risk of exposure to Legionella in the domestic hot water system. These findings highlight the importance of adequate preopening cleaning and disinfection procedures for hotel water systems, and the convenience of considering the most effective disinfection methods especially for hot water systems and after prolonged closure periods.